Analisis Bibliometrik: Publikasi Ilmiah Perancangan Sistem Informasi di Indonesia - Moh. Hanif Mubarok; Purdiyastomo, Pandumukti (Pustabiblia: Journal of Library and Information Science, 2024)
This research conducted a bibliometric analysis of publications related to information systems design in Indonesia during the period 2019-2023. Using data from Google Scholar as well as Publish or Perish and VOSviewer tools, this research maps and analyzes trends, patterns, and dynamics in this field. Key findings include the identification of the most influential articles, researcher productivity mapping, and co-occurrence analysis that revealed 44 topic clusters. “Application of Waterfall Method in Designing Web-Based Project Monitoring Information System” is the article with the highest citations (1394), while “Budiman, A.” and “Damayanti, D.” are the most productive researchers. Network and density visualizations show the dominance of certain terms and identify opportunities for future research. This research provides a comprehensive understanding of the information systems design research landscape in Indonesia, and highlights gaps and opportunities for future research.